(3GdLQjeI GdefXeI hBdjGJ ecGaMJgG aj VhA KhQI GdGJUGdGJ hGdJcfhdhLjG GdMOjKI (B/s - (3ScQ, YHO GdUeO YHO GdYRjR,s 1959- ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3GdLQjeI GdefXeI hBdjGJ ecGaMJgG aj VhA KhQI GdGJUGdGJ hGdJcfhdhLjG GdMOjKI(B) (3hGdPj bGe HJCdjag (B((3YHO GdUeO ScQ(B) (3aj MhGdj (B(254) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3ecGaMI GdLQGFe GdefXeI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI, GdaUd GdChd (B: (3eGgjI GdLQjeI GdefXeI, GdaUd GdKGfj (B: (3GdLQjeI GdefXeI hHYV GdLQGFe GdCNQi GdeQJHWI, GdaUd GdKGdK (B: (3BdjGJ ecGaMI GdLQjeI GdefXeI(B... (3EdN(B.s
(3ebQQGJ OQGSjI (B2025-2026.s
(3HHdjhLQGajI (B: (3UaMI (B233-252.s
Keywords: (3ecGaMI GdLQjeIs -- (3eYGdLI HjGfGJs; (3GdLQGFe GdefXeIs -- (3hbGjIs -- (3eYGdLI HjGfGJs